Rumoh Aceh as regional identity in office buildings in Banda Aceh/ Cut Nursaniah, Zahriah Zahriah and Masdar Djamaludin - Nursaniah, Cut; Zahriah, Zahriah; Djamaludin, Masdar (Universiti Teknologi MARA, Perak, 2023)
The traditional architecture of Rumoh Aceh has developed over a long time and has become the identity of the people in Aceh. One way to keep the architecture of Rumoh Aceh alive in this era of global modernization is to transform it into an office building in the area, to a form of regional identity. This paper aims to examine efforts to apply the architectural identity of Rumoh Aceh to office buildings in the center of Banda Aceh City because ideally office buildings contribute as architecture that gives the image of a region. The four office samples were determined based on the maximum percentage of styles in Rumoh Aceh, from the initial studies that were conducted. The collected data were analyzed based on archetype theory, and evidence of acculturation of Traditional Architecture and Modern Architecture due to developments in technology and building materials. The application of the Rumoh Aceh style to offices tends to adopt a dominant and easily visible form (roof shape, pit shape, elevation of the center, entrance, carving), as a building identity and aesthetic function. The architectural appearance tends to be original from aspects related to shape, form and architectural style, because their applications have not been supported by adequate theory, methods and transformation techniques.